Bimbingan Motorik Anak Melalui Senam Anak Indonesia Hebat Di Sekolah Menengah Pertama Negeri 12 Kota Bengkulu - Putra, Dwingki Marta; Lismana, Oetari; Apriansyah, Dolly; Lemos, Ramos; Setiawan, Aryo; Afrianzah, Aceyf (Jurnal Dehasen Untuk Negeri, 2025)
SMP Negeri 12 Kota Bengkulu is located in Bengkulu City, precisely in Lempuing Village, where every first Friday of the month there will be a sports activity, namely gymnastics together with the material of Indonesian Great gymnastics, which is attended directly by all teachers and staff and children at SMP Negeri 12 Kota Bengkulu. From this, the Physical Education Lecturer of Dehasen University conducted Community Service with the Theme: Children's Motor Guidance Through Indonesian Great Gymnastics at SMP Negeri 12 Kota Bengkulu.